Ten-Year Mortality Trends for Adults with and without Diabetes Mellitus in South Korea, 2003 to 2013 - Kyeong Jin Kim; Tae Yeon Kwon; Sungwook Yu; Ji A Seo; Nan Hee Kim; Kyung Mook Choi; Sei Hyun Baik; Dong Seop Choi; Sin Gon Kim; Yousung Park; Nam Hoon Kim (Diabetes & Metabolism Journal, 2018)
BackgroundTo estimate and compare the trends of all-cause and cause-specific mortality rates for subjects with and without diabetes in South Korea, from 2003 to 2013.MethodsUsing a population-based cohort (2003 to 2013), we evaluated annual mortality rates in adults (≥30 years) with and without diabetes. The number of subjects in this analysis ranged from 585,795 in 2003 to 670,020 in 2013.ResultsAge- and sex-adjusted all-cause mortality rates decreased consistently in both groups from 2003 to 2013 (from 14.4 to 9.3/1,000 persons in subjects with diabetes and from 7.9 to 4.4/1,000 persons in those without diabetes). The difference in mortality rates between groups also decreased (6.61 per 1,000 persons in 2003 to 4.98 per 1,000 persons in 2013). The slope associated with the mortality rate exhibited a steeper decrease in subjects with diabetes than those without diabetes (regression coefficients of time: −0.50 and −0.33, respectively; P=0.004). In subjects with diabetes, the mortality rate from cardiovascular disease decreased by 53.5% (from 2.73 to 1.27 per 1,000 persons, P for trend <0.001). Notably, the decrease in mortality from ischemic stroke (79.2%, from 1.20 to 0.25 per 1,000 persowns) was more profound than that from ischemic heart disease (28.3%, from 0.60 to 0.43 per 1,000 persons).ConclusionAll-cause and cardiovascular mortality rates decreased substantially from 2003 to 2013, and the decline in ischemic stroke mortality mainly contributed to the decreased cardiovascular mortality in Korean people with diabetes.